2011
DOI: 10.1080/15567265.2010.502925
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Sensitivity of Microcantilevers in the Mid-Infrared Spectral Region

Abstract: This article reports the thermomechanical sensitivity of bimaterial cantilevers over a midinfrared (IR) spectral range (5-10 µm) that is critical both for chemical analyses via vibrational spectroscopy and for direct thermal detection in the 300-700 K range. A physicsbased model of cantilever bending was developed by including heat transfer to and within the cantilever, temperature-dependent cantilever bending, and cantilever and optical system IR characteristics. Detailed measurements of the optical system IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although the PCDS signal can be further increased by enhancing the thermal sensitivity of the microcantilever as well as by increasing the impinging power of IR, we should take thermomechanical noise, a dominant noise source for PCDS, into account in order to evaluate SNR which determines the limit of detection2324. The root mean square amplitude of cantilever deflection from thermomechanical noise at well below the resonance frequency is given by25 where k B is the Boltzmann constant, T is the absolute temperature, B is the measurement bandwidth, Q is the quality factor, k is the spring constant, and ω 0 is the angular resonance frequency of the cantilever.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PCDS signal can be further increased by enhancing the thermal sensitivity of the microcantilever as well as by increasing the impinging power of IR, we should take thermomechanical noise, a dominant noise source for PCDS, into account in order to evaluate SNR which determines the limit of detection2324. The root mean square amplitude of cantilever deflection from thermomechanical noise at well below the resonance frequency is given by25 where k B is the Boltzmann constant, T is the absolute temperature, B is the measurement bandwidth, Q is the quality factor, k is the spring constant, and ω 0 is the angular resonance frequency of the cantilever.…”
Section: Discussionmentioning
confidence: 99%
“…Apertures have been employed for decades and the technology 26,27 has been essentially unaltered since the advent of Fourier transform infrared (FT-IR) microscopy. While scanning probes have received considerably more attention for nanoscale spectroscopic mapping, their use for microscale measurements 28,31 is generally useful only to localize signal from specific regions or samples 32 and not for large area mapping. IR imaging typically refers to the use of multichannel detectors to achieve spatial localization, which enables recording a reasonably sized image in short times.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The bimaterial cantilevers have shown a potential as a novel uncooled IR detector by exhibiting IR sensitivity similar to traditional methods but with lower cost and faster response time ($0.1-1 ms). 1,11,12 Published research has shown that a bimaterial cantilever can detect radiative power of 250 pW/Hz 0.5 at the wavelength of 650 nm, 6 or 1.3 nW/Hz 0.5 at the wavelength of 10 lm.…”
Section: Introductionmentioning
confidence: 99%